The Effect of Self-Efficacy, Self-Concept, Learning Activities and Independent Learning on Mathematics Learning Achievements - Ernawati, Ernawati (Universitas Negeri Makassar, 2020)
This study aimed to find out (1) the description of self-efficacy, self-concept, learning activities, independent learning, and mathematics learning achievements, (2) the effect of self-efficacy on students’ mathematics learning achievements directly and indirectly through independent learning, (3) the effect of self-concept on students’ mathematics learning achievements directly and indirectly through independent learning, (4) the effect of learning activities on students’ mathematics learning achievements directly and indirectly through independent learning. The population was students at SMPN in Somba Opu sub-district. Data were collected through 284 students as the samples of the study selected by employing equal size cluster random sampling technique. Data were analyzed by using descriptive statistics analysis and path analysis. The results of the study revealed that (1) most of grade VII students at SMPN in Somba Opu sub-district have self-efficacy with high category, self-concept with high category, learning activities with extremely high category, independent learning with high category, and mathematics learning achievements with high category, (2) self-efficacy positively and significantly affect on mathematics learning achievements directly and indirectly through independent learning, (3) self-concept positively and significantly affect on mathematics learning achievements directly and indirectly through independent learning, and (4) learning activities positively and significantly affect on mathematics learning achievements directly and indirectly through independent learning